Constructing the mafia concept on the bench. The legal battles in the 'Mafia Capitale' case in Rome. (September 2019) - Sergi, Anna
Abstract: The Italian Antimafia Operation 'Mondo di Mezzo' (the World in Between) has presented the group called "Mafia Capitale" as a mafia-type group born and bred in Rome, with its own mandate and reach into public administration and politics. A maxi-trial established that the corruptive method employed by associates of Mafia Capitale, together with the entrepreneurial nature of the group, were enough to qualify the group as a mafia-type criminal association within the scope of article 416-bis of the Italian Penal Code. Starting from considerations on legal constructivism, this paper compares juridical documents by the Antimafia Prosecutors and the first degree Tribunal to explore the diversity of their legal arguments. The paper will argue that considering systemic corruption as strategy of intimidation and manifestation of mafia power in contemporary days is imperative to evolve the concept of mafia itself.